FISCAL AND REGULATORY ASPECTS OF INCOME TAX ADMINISTRATION IN WARTIME CONDITIONS - Novosolova , O. S. (The actual problems of regional economy development, 2024)
The relevance of the study is determined by the fact that the income tax is a significant source of filling budgets and an important tool for regulating business activity. The substantiation of the directions for optimization of the tax policy of the state in relation to the taxation of the income of economic entities in the conditions of the destructive influence of the war acquires special importance. The purpose of the article is to assess the fiscal significance and implementation of income tax regulatory impact in Ukraine, as well as to determine recommendations on ways to increase the effectiveness of income taxation in the context of stimulating investment processes and expanded reproduction. The fiscal significance of income tax in the formation of the consolidated budget was determined, the dynamics and composition of tax revenues of the State Budget of Ukraine were analyzed, and the structure of income tax revenues by payers types was evaluated. The factors of reducing the budget-forming role of income tax are outlined. The main efficiency indicators of the income tax fiscal potential realization in Ukraine have been studied. It was revealed that against the background of permanent growth of income tax revenues of enterprises to the consolidated budget, the size of the effective tax rate showed a trend opposite to the dynamics of the financial result before taxation. The overall level of the tax burden on the economy of Ukraine and the tax burden from the income tax in particular was assessed. On the basis of the conducted research, it was concluded that the current mechanism of income taxation is characterized by the complexity of calculating the amount of tax liabilities and the preparation of financial statements, the presence of wide opportunities for the use of tax avoidance and evasion schemes, the instability of tax legislation, as well as the inability to provide a stimulating effect on processes of encouraging entrepreneurial activity, increasing the need to attract foreign investments and achieving a high level of population employment. It is proposed to transform the income tax gradually into a tax on the withdrawn capital which will allow to optimally combine the instruments of regulatory potential, maximize the final performance indicators of enterprises, balance the tax burden on business and ensure the implementation of the fiscal component of the tax.